Risk Factors for Asymptomatic Enteric Pathogen Detection Among Men Who Have Sex With Men. (11th July 2019) - Williamson, Deborah A; Chow, Eric P F; Lee, Darren; Maddaford, Kate; Sait, Michelle; Easton, Marion; Ingle, Danielle; Wigan, Rebecca; De Petra, Vesna; Howden, Benjamin P; Fairley, Christopher K; Chen, Marcus Y
Abstract: Improved knowledge of factors that promote outbreaks of enteric pathogens among men who have sex with men (MSM) could enable targeted public health interventions. We detected enteric pathogens in 57 of 519 (11%) asymptomatic MSM, and we found that enteric pathogen detection was associated with both oroanal sex (rimming) and group sex.